Keberlanjutan UMKM Desa Morowudi Melalui Pelatihan Manajemen Keuangan - Aristha Purwanthari sawitri; M. Afrizal Miradji; Noerchoidah; Untung Lasiyono (Fakultas Ekonomi, Universitas PGRI Adi Buana Surabaya, 2022)
The business owner is fully responsible for the business being run. Decisions made by business owners must be right to overcome and resolve problems that occur. Financial knowledge helps business owners to produce good financial management and business development behavior. The main factor for MSME snacks in Cerme District, Gresik Regency not being able to develop is the lack of knowledge about financial knowledge and financial management. Therefore, training and assistance is needed regarding financial knowledge and financial management for snack food MSME in Cerme District, Gresik Regency so that business owners are able to plan, analyze, supervise business finances. Service activities can encourage business owners to better understand current financial conditions so that business owners can minimize the risk of financial difficulties caused by environmental changes.